Altitude tracking using colour marker based navigation system for image guided surgery - Saaidon, Nur'Ain; Sediono, Wahju; Sophian, Ali (Conference Publishing Services, 2016)
Optical tracking method has been largely used for medical navigation system in Robotic Image Guided Surgery (IGS). One of the methods proposed by recent researcher is to use colour feature as the marker for medical instruments detection and tracking. Since IGS system is using preoperative imaging data set for reference, unintended patient movement can result in major errors. In this work, the position for the medical instrument’s marker is being investigated to prove that the method can be used for tracking in navigation system. Moving target marker will represent the unintended patient movement. The tool marker will be navigated autonomously using robotics arm to adjust the changes. Multithreading programming approach is being implemented in the system to increase the position update rate for real-time application. The system is able to track the markers and navigate the tool marker to the target marker with certain error tolerance. The accuracy and performance of the system are still in the need of some improvements.